From dissection to diagnosis: enhancing anatomy through clinical collaboration - Azmi, Muhammad Fairuz; Ab Mumin, Nazimah (Faculty of Medicine, 2025)
On 1 July 2025, the Department of Anatomy successfully conducted a session under the Collaborative Group for Collaborative Teaching (CGCT) initiative as part of the Clinical Anatomy slot for the MBBS Year 1 Urinary System module. The session served as the culmination of a series of foundational lectures and practical sessions covering the gross anatomy and histology of the urinary system. Students had previously explored the kidneys, ureters, bladder, and urethra through lectures, cadaveric demonstrations, and histological slide reviews.